A Rebel among Redcoats a Revolutionary War novel - Gunderson, Jessica (North Mankato, Minnesota Stone Arch Books, A Capstone Imprint, 2015)
In 1780 South Carolina thirteen-year-old Maggie believes in the American cause, but after her father is seized by the British she is forced to live with her loyalist aunt in Charles Town--but when the British capture the city Maggie is determined to get information to Colonel Francis Marion
A gift from book Africa
English stories
1 2 13 15
Keywords: Marion, Francis -- 1732-1795; Marion, Francis -- 1732-1795 -- Fiction